Bioequivalence of oxymorphone extended release and crush-resistant oxymorphone extended release - Fiske WD; Xiang Q; Jobes J; Benedek IH (Dove Medical Press, 2011)
Irma H Benedek, Janet Jobes, Qinfang Xiang, William D Fiske Endo Pharmaceuticals Inc, Chadds Ford, PA, USA Background: A formulation of crush-resistant extended-release opioids may deter abuse. The purpose of this study was to evaluate the bioequivalence of oxymorphone extended-release (Oxy-ER) and a crush-resistant formulation of oxymorphone extended-release (Oxy-CRF). Methods: In three open-label, randomized studies, healthy adults at a clinical research center received two single oral doses of Oxy-ER and two single doses of Oxy-CRF, each separated by a ≥7-day washout. Doses were administered under fasted conditions (study 1, 5 mg doses; study 2, 40 mg doses) or after a high-fat breakfast (study 3, 40 mg doses). Subjects administered 40 mg doses also received naltrexone. The primary endpoint was systemic oxymorphone exposure; the bioequivalence criterion was met if the 90% confidence intervals of the geometric mean ratio (Oxy-CRF/Oxy-ER) for oxymorphone area under the curve from time 0 to the last measured concentration (AUC0–t), AUC from time 0 to infinity (AUC0–inf), and maximum plasma concentration (Cmax) were within 0.8–1.25. Safety was assessed by monitoring adverse events. Results: In studies 1, 2, and 3, the safety population comprised 30, 37, and 36 subjects and the pharmacokinetics population comprised 27, 30, and 29 subjects, respectively. Oxy-ER and Oxy-CRF produced similar mean ± standard deviation oxymorphone AUC0–t (study 1, 5.05 ± 1.55 versus 5.29 ± 1.52 ng · h/mL; study 2, 31.51 ± 10.95 versus 31.23 ± 10.33 ng · h/mL; study 3, 50.16 ± 14.91 versus 49.01 ± 14.03 ng · h/mL) and Cmax (0.38 ± 0.11 versus 0.37 ± 0.12 ng/mL; 2.37 ± 1.20 versus 2.41 ± 0.94 ng/mL; 5.87 ± 1.99 versus 5.63 ± 2.26 ng/mL) under all conditions. The 90% confidence intervals for plasma oxymorphone AUC0–t, AUC0–inf, and Cmax fulfilled the bioequivalence criterion. Adverse event rates were similar with Oxy-ER and Oxy-CRF (study 1, 25% versus 23%; study 2, 9% versus 16%; study 3, 20% each group). Conclusion: Oxy-CRF and Oxy-ER (5 mg and 40 mg) are bioequivalent under fasted and fed conditions, suggesting that Oxy-CRF will have clinical efficacy and safety equivalent to Oxy-ER. Keywords: abuse deterrent, bioequivalence, opioid, oxymorphone, pharmacokinetics, substance abuse